The determination of the thickness and optical constants of the ZnO crystalline thin film by using envelope method - Caglar, M; Caglar, Y; Ilican, S (Journal of Optoelectronics and Advanced Materials, 2006)
ZnO crystalline thin film has been deposited onto glass substrates by the spray pyrolysis method. The crystallographic structure of the film and the size of the crystallites in the film were studied by X-ray diffraction. XRD measurement shows that the film is crystallized in the wurtzite phase and presents a preferential orientation along the c-axts. Only one peak, corresponding to the (0 0 2) phase (20=34.760), appears on the diffractograms. An envelope method, based on the optical reflection spectrum taken at normal incidence, has been successfully applied to the geometrical-optical characterization of thin films having significant surface roughness. Such a method allows the determination of the average thickness and the refractive index of the films with accuracies better than 1%, as well as the average amplitude of the surface roughness with an accuracy of about 2%. Optical constants such as refractive index n and extinction coefficient k, were determined from transmittance spectrum in the ultraviolet-visible-near infrared (UV-VIS-NIR) regions using envelope methods. Absorption coefficient a, and the thickness of the film t were calculated from interference of transmittance spectra. The energy band gap, and the thickness of the films were evaluated as 3.283 eV and 635 nm, respectively.